THE PROBATION MEASURES – THE REASONS FOR THE REGULATION - Andrei-Dorin BĂNCILĂ (Challenges of the Knowledge Society)
For a proper understanding of the law institution, it is necessary to understand the reasons that gave rise to the its regulation. By reasons of regulations, we understand the social, economic, political, legal, moral justifications, but also of any other nature that established the legislation adoption represents a positive source of the institution in question. Trying to find reasons for the regulation is a useful step, even under stronger word, if the institution researched is relatively new in the normative context, character that can be easily subject to error, assigned to the probation measures into Romanian law. The utility of teh step is to know the circumstances that caused, encouraged or even imposed the settlement of the probation measures in our country, but also of the goals that the new institution will answer them.